2023
DOI: 10.3390/su151813314
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Asphalt Mixtures Containing Different Proportions of Alternative Materials

Meisam Khorshidi,
Ahmad Goli,
Marko Orešković
et al.

Abstract: With the increasing scarcity and cost of virgin materials for asphalt mixtures, the exploration of alternative components has intensified. Reclaimed asphalt pavement (RAP), crumb rubber (CR), steel slag (SS), and waste engine oil (WEO) have emerged as promising alternatives. Individually, RAP enhances rutting resistance but may compromise cracking tolerance; CR boosts cracking resistance; WEO affects cracking and rutting differently; and SS can influence moisture sensitivity. However, their combined impacts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The adhesiveness of an asphalt mixture is determined from the bond of the aggregate-binder system, and water damage can occur under two conditions: (a) when the asphalt binder loses adhesive properties, or cohesion occurs; (b) when the aggregate-binder adhesiveness is reduced. Both conditions result in stripping, which weakens the adhesion between the asphalt binder and the aggregate particles, thus affecting the chemical composition and their bond [22]. Therefore, the specific properties of these materials, as well as the properties of the mixture, significantly impact the performance of the asphalt pavement [23].…”
Section: Indirect Tensile Strength On Moisture Damagementioning
confidence: 99%
“…The adhesiveness of an asphalt mixture is determined from the bond of the aggregate-binder system, and water damage can occur under two conditions: (a) when the asphalt binder loses adhesive properties, or cohesion occurs; (b) when the aggregate-binder adhesiveness is reduced. Both conditions result in stripping, which weakens the adhesion between the asphalt binder and the aggregate particles, thus affecting the chemical composition and their bond [22]. Therefore, the specific properties of these materials, as well as the properties of the mixture, significantly impact the performance of the asphalt pavement [23].…”
Section: Indirect Tensile Strength On Moisture Damagementioning
confidence: 99%
“…Bekheda et al [13] also examined asphalt mixtures containing PET in varying percentages (3%, 5%, and 7%) and concluded that it improves the resistance of asphalt to permanent deformation. Also, according to Khorshidi et al's study, the mechanical characteristics of asphalt mixtures containing different proportions (0%, 2%, 4%, 6%, 8%, and 10%) of PET demonstrated enhanced properties, including increased stiffness, stability, and viscosity [14]. Moreover, adding polyethylene to asphalt modification improved resistance against fatigue and deformation.…”
Section: Introductionmentioning
confidence: 96%
“…Asphalt drainage pavement is mainly composed of large voids and open-graded asphalt mixture, thus forming a spatial skeleton-void structure, which can provide greater compressive strength [11][12][13]. Due to the suspension of open-graded aggregates and the small contact position between the aggregates, ordinary asphalt struggles to provide an effective bonding effect, therefore requiring a high-viscosity modifier to increase the asphalt-bonding effect as well as the overall strength of the pavement [9,14].…”
Section: Introductionmentioning
confidence: 99%